Reliability and validity of prognostic indicators for Guillain–Barré syndrome in children. (29th September 2022) - Qinrong, Huang; Yuxia, Chen; Ling, Liu; Huayu, Luo; Lei, Xu; Xiaoli, Li; Nong, Xiao
Abstract: Aim: To explore the clinical characteristics and prognostic predictors of Guillain–Barré syndrome (GBS) in Chinese paediatric patients. Method: The clinical features of children with GBS hospitalized in the Children's Hospital of Chongqing Medical University were summarized retrospectively. The correlation between the Erasmus GBS Outcome Score (EGOS)/modified Erasmus GBS Outcome Score (mEGOS), GBS disability score (GDS)/modified Rankin Scale (MRS), Erasmus GBS Respiratory Insufficiency Score (EGRIS), and mechanical ventilation were evaluated. Results: One hundred forty‐two patients (86 males, 56 females; median 62.50 months [interquartile range 41.00–97.50]) with classic GBS were enrolled in the study. In the present GBS cohort, 134 (94.37%) patients could walk independently (GDS ≤2) and 121 (85.21%) could manage without assistance (MRS ≤2) at 6 months. Eighteen (12.68%) patients with GBS required mechanical ventilation. The performance of mEGOS on admission, mEGOS on day 7, and EGOS‐predicted GDS outcome at 4 weeks, 3 months, and 6 months in the paediatric patients with GBS admitted within 2 weeks of disease onset and that of the MRS outcome were evaluated. The EGRIS in individuals who required mechanical ventilation was significantly higher than in patients without mechanical ventilation (median = 6 vs median = 3, p  < 0.001). Interpretation: In Chinese paediatric patients with GBS who were admitted 2 weeks after disease onset, the mEGOS and EGOS are validated indicators for the prediction of clinical outcomes 6 months after onset. EGRIS is helpful in predicting the implementation of mechanical ventilation in the acute phase. What this paper adds: The Erasmus Guillain–Barré syndrome (GBS) Outcome Score (EGOS) and modified EGOS are reliable prognostic predictors in paediatric patients with GBS. The Erasmus GBS Respiratory Insufficiency Score (EGRIS) is an effective predictor of mechanical ventilation in paediatric patients with GBS. An EGRIS of ≥5 indicates a high risk of mechanical ventilation in the acute phase. What this paper adds: The Erasmus Guillain–Barré syndrome (GBS) Outcome Score (EGOS) and modified EGOS are reliable prognostic predictors in paediatric patients with GBS. The Erasmus GBS Respiratory Insufficiency Score (EGRIS) is an effective predictor of mechanical ventilation in paediatric patients with GBS. An EGRIS of ≥5 indicates a high risk of mechanical ventilation in the acute phase. The Erasmus Guillain–Barré syndrome (GBS) outcome score (EGOS) and modified EGOS are reliable prognostic predictors in paediatric patients with GBS; mEGOS‐D7 ≥5.0 and EGOS ≥3.5 indicate poor GDS prognosis at 6 months,  and mEGOS‐OA ≥2.5,  mEGOS‐D7 ≥7.5 and EGOS ≥3.5 for MRS.The Erasmus GBS Respiratory Insufficiency Score (EGRIS) is an effective predictor of mechanical ventilation in paediatric patients with GBS.An EGRIS ≥5 indicates a high risk of mechanical ventilation in the acute phase. This original article is commented on by Misra on pages 448–449 of this issue.